2022
DOI: 10.1111/cns.14041
|View full text |Cite
|
Sign up to set email alerts
|

Contemplating IL‐6, a double‐edged sword cytokine: Which side to use for stroke pathology?

Abstract: Interleukin (IL)‐6 is a unique cytokine due to its dual signaling, with one pathway being pro‐inflammatory (trans) and the other homeostatic (classical). Both of these pathways have been implicated in neuroinflammation following stroke, with initial inflammatory mechanisms being protective and later anti‐inflammatory signaling promoting ischemic tissue recovery. IL‐6 plays a major role in stroke pathology. However, given these distinctive IL‐6 signaling consequences, IL‐6 is a difficult cytokine to target for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 61 publications
0
5
0
1
Order By: Relevance
“…Mulia et al reported that AF developed in 66% of patients who developed pericarditis and myocarditis as a result of local inflammation in patients with Barrett's esophagus 18 . Inflammation-associated AF was correlated with an increase in circulating inflammatory cytokines 19 . Hiatal hernia mechanically compresses the left atrium.…”
Section: Discussionmentioning
confidence: 98%
“…Mulia et al reported that AF developed in 66% of patients who developed pericarditis and myocarditis as a result of local inflammation in patients with Barrett's esophagus 18 . Inflammation-associated AF was correlated with an increase in circulating inflammatory cytokines 19 . Hiatal hernia mechanically compresses the left atrium.…”
Section: Discussionmentioning
confidence: 98%
“…In the trans-signaling pathway, soluble IL-6R (sIL-6R), generated by IL-6R cleavage from the membrane (by the proteases ADAM [Disintegrin and Metalloproteinase] 10 and/or ADAM 17) or via alternative splicing (in humans), binds to the secreted IL-6. The sIL-6R-IL-6 complex binds to and activates gp130 [ 245 , 246 ]. While IL-6R expression is cell-type-restricted, gp130 is expressed ubiquitously; therefore, classic IL-6 signaling is restricted to IL-6R-expressing cells, whereas trans-signaling can occur in any cells.…”
Section: Tmev Infection In a Mouse Model Of Viral-induced Seizures An...mentioning
confidence: 99%
“…Both pathways lead to the phosphorylation of STAT3, but trans-signaling exhibits a more sustained and higher amplitude response. Notably, classic signaling is associated with protection and anti-inflammatory properties, while trans-signaling exhibits pathological and pro-inflammatory roles [ 245 , 246 ]. Thus, it is important to recognize that IL-6R inhibitors cannot differentiate between classic and trans-signaling, blocking both pathways and potentially leading to unexpected and detrimental side effects.…”
Section: Tmev Infection In a Mouse Model Of Viral-induced Seizures An...mentioning
confidence: 99%
“…(pro-inflammatory cytokines)으로 [18], 뇌졸중 치료에 있어서 증가 또는 감소의 이점에 대해 상충되는 보고가 존재하기 때문이다 [19]. 허혈성 및 출혈성 뇌졸중 발병 이후 IL-6 수준은 염증 반응으로 인해 증가하는데 [20,21], 높은 IL-6 수준은 전통적으로 불리한 예후로 간주 되며 짧은 생존 기간 [22], 높은 섬망 위험 [23], 단기 기 능적 결과 및 손상 크기 [24]와 관련이 있는 것으로 보고 되었다.…”
Section: Il-6는 염증을 악화시키거나 조직의 회복을 촉진할 수 있는 양면적 특징을 지닌 전 염증성 사이토카인unclassified